Drawing and Memory: What is the Content of Children's Drawings and How Does it Differ From Their Verbal Reports?. (July 2022) - Iordanou, Christiana; Allen, Melissa L.; Warmelink, Lara
This study investigated whether the content of children's drawings of an event changes over three successive interviews about that event. It also assessed whether children recall more details verbally than they draw. Twenty-seven 3- to 6-year old children witnessed a live event which ended with one actor stealing a cuddly toy. They were interviewed about it 1 day, 2 weeks, and 6 months later. At each interview, children were asked to make a drawing of the event while narrating what happened. We analyzed the content of the drawings for seven features relevant to the event as well as inaccurate information. Children's inclusion of "the perpetrator" and "the victim" decreased over time but the other features remained stable. Children verbally reported significantly more details than they drew. Our findings suggest that children provide less information in drawings than in verbal reports, but this information may be more reliable and stable compared to verbal reports over multiple interviews.